Urban land dispute and resolution mechanisms in two selected Ethiopian towns; from good governance perspective - Udessa, Fraol; Adugna, Dagnachew (Frontiers in Built Environment, 2026)
The main objective of this paper is to examine Urban Land Dispute and Resolutions in two selected Ethiopian Towns from Governance perspective. Land tenure is widely recognized as vital to social security, sustainable development, economic growth and effective government. To achieve this objective a mixed methods research approach was used. Data were collected from 391households through questionnaires, 22 key interviews and two focus group discussions and analyzed descriptively. According to the study results, boundary disputes, expropriation of property rights based on false evidence, real estate loans, granting of use rights and illegal sale of urban land were the main causes of urban land disputes. The conflict resolution system was inadequate to protect the rights of vulnerable groups and public property. Judges were unable to interpret and apply land law because it was not an integral part of legal training. As a result, the quality of judgments was ultimately compromised by the fact that city-level judges were less qualified and experienced than higher court judges. Furthermore, the responsibility for conflict resolution at various levels has not been delegated to the actual practices of cities. In addition, there was a local informal dispute resolution system that occasionally made unfair decisions, but due to the development plan, it was never taken into account by the administrative dispute resolution system. Questions over city lands persisted in the first instance and in regional high courts for many years because disagreements could not be quickly resolved in the formal system. Finally, limiting the various forms of dispute resolution requires legal scrutiny and increases the ability of regional arbitration organizations to resolve disputes quickly and cost-effectively by providing them with access to training, legal resources and office space.